1995
DOI: 10.1002/qua.560560517
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects in density functional calculations of uracil and cytosine tautomerism

Abstract: mThe effects of the solvent on the tautomeric equilibria of cytosine and uracil are studied using Onsager's reaction field model in the framework of density functional theory. In this model, the solute molecule is placed in a spherical cavity of radius a, immersed in a continuous medium with a dielectric constant E , treating the solute-solvent electrostatic interactions at the dipole level. The cavity radius is evaluated by determining the molecular volume with a quantum mechanical approach. The solvent effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 37 publications
(15 reference statements)
7
48
0
Order By: Relevance
“…At B3LYP/6-31+G ** level of theory, the most stable tautomer is 1,3-U, followed by 2 1 ,3-U, 1,4 1 -U, 2 1 ,4 1 -U, 2 2 ,4 1 -U, 2 1 ,4 2 -U, 2 2 ,4 2 -U, 1,4 2 -U, 2 2 ,3-U, 1,2 2 -U, 3,4 2 -U, 3,4 1 -U, and 1,2 1 -U. This order is consistent with former studies [30,35,42]. High level ab initio methods give not only considerable differences in relative energy values, but also change the stability order [51].…”
Section: The Stability Order Of Uracil and Diphosphouracil Tautomerssupporting
confidence: 92%
“…At B3LYP/6-31+G ** level of theory, the most stable tautomer is 1,3-U, followed by 2 1 ,3-U, 1,4 1 -U, 2 1 ,4 1 -U, 2 2 ,4 1 -U, 2 1 ,4 2 -U, 2 2 ,4 2 -U, 1,4 2 -U, 2 2 ,3-U, 1,2 2 -U, 3,4 2 -U, 3,4 1 -U, and 1,2 1 -U. This order is consistent with former studies [30,35,42]. High level ab initio methods give not only considerable differences in relative energy values, but also change the stability order [51].…”
Section: The Stability Order Of Uracil and Diphosphouracil Tautomerssupporting
confidence: 92%
“…Similar behaviors have been found at the MP2 30 level and with previous DF computations on cytosine. 6 In the protonated molecules the amine groups are nearly planar. As a general feature we note that our bond lengths and valence angles agree well with the experimental data and are consistent with MP2-optimized structures.…”
Section: Structural Featuresmentioning
confidence: 99%
“…In fact, the most stable DF tautomer is always the one with the hydrogen bonded to the nitrogen to which the sugar moiety of nucleosides is attached. On the other hand, in the case of cytosine, the energy differences between the most stable tautomer proposed by the ab initio study 3 and that coming from the previous DF computation 6 is about 1 kcalrmol and does not significantly affect the PA values.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6] Vigorous efforts are being made to understand the structures and properties of a variety of biomolecules including the nucleic acid bases using theoretical and spectroscopic methods. [3][4][5][6][7][8][9][10][11][12] Electronic structure calculations, 13,14 simulation, 15,16 and studies of solvent effects [17][18][19][20] have been carried out on several systems, including the nucleic acid bases and other biologically important molecules. It is found that behaviors of biomolecules in aqueous media may be appreciably different from those in crystals.…”
Section: Introductionmentioning
confidence: 99%